The Leader's Statement in Kurinji Thinai - T, Manimozhi (International Research Journal of Tamil, 2022)
Literature excels in capturing the essence of life that has not been dissolved by the flood of time. In that way, the respective chronicles have well recorded all the biographies of the Tamils. Palandamizhar's life is departmental. Tamils set up a lifestyle appropriate to the place and conveyed the excellence of the lifestyle through literature. In this way, the stories of Kurinji land life in hilly areas are abundantly reported in Sangam literature. This article examines the claims of the Kurinchi land chief. In human life, language separates man from other creatures and elevates this species to a higher level. The statements are made to reveal the elements of inner life. Through this article, it is possible to know that the mental consciousness of the leader is revealed.